Penerapan online social convergence dalam pemberitaan bencana: analisis konten kualitatif pada situs web disasterchannel.co - Adhika Pertiwi; Zainuddin Muda Z Monggilo (Jurnal Komunikasi Profesional, 2022)
When a natural or human-caused disaster occurs in the rapid digital development era, the phenomenon of massive dissemination of information from citizen journalism emerges. This research uses the qualitative approach to describe online social convergence in disasterchannel.co, a disaster portal website where most of the articles come from citizen journalism. A total of 15 articles were reviewed with content analysis to understand the application of online social convergence in disaster reporting, which consists of seven aspects: helping; being anxious; returning; supporting; mourning; exploiting, and being curious. In general, seven aspects of online social convergence have been applied in the article published by disasterchannel.co. The most often aspect that appears are supporting and helping. This study shows that disasterchannel.co has implemented online social convergence through citizen journalism articles published on their website.